Brain Hydatidosis surgical outcome (Medico Legal Update, 2021)
Background: Brain Hydatidosis is one of common parasitic brain diseases accounted in Iraq. This isprospective study done in mosul teaching hospital in Iraq during 2007-2020.Material and Method: All patient data had collected from the records of 19 patients admitted to Mosulcenter with hydatidosis, including clinical features and imaging investigation in addition to operative record.Follow up of all included patient was achieved.Results: Ninteen patients were included, twelve male and seven female . Eighteen patients were of intracerebralhydatidosis while one was extradural. Eight patients in parietal lobe, five patients in frontoprietal lobe,,threepatients in occipital lobe, two in cerebellum and one patient in frontal. Age ranged 3-45 years where sixteenpatients were children. Three patients get multiple cysts while the other sixteen get solitary hydatid cyst. Allpatients were treated by craniotomy and total excision (delivery) of hydatid cyste(s) while rupture occurredon one case and albendazole had given for all of patients postoperativly. All patients except two get retuneto normal neurological function while one still in deficit the other one died due to postoperative infection.No recurrence was seen.Conclusion: Brain hydatidosis is still seen in our country and early surgery provide good treatment inaddition to use of albendazole while mortality and morbidity are not uncommon postoperative events.